Dynanic Simulation of Helical Gears with Crack Propagating In to Gear Body*. Issue 2 (February 2020) - Jiang, Hanjun; Liu, Fuhao; Wang, Manlin
Abstract: The change of mesh stiffness induced by tooth crack will change the vibration characteristic of gear system. In this paper, an analytical model is proposed to investigate the helical gear mesh stiffness with tooth crack propagating into gear body. The developed model is validated by comparison with the FEA method. Hereafter, the mesh stiffness of helical gears with different crack depths is obtained and the effect of the crack depth on the mesh stiffness is studied. Afterwards, a 6 DOF helical gear dynamic model is established and the effects of crack depth on the dynamic response are investigated. The results indicated that the mesh stiffness of the helical gears reduced significantly with the present of tooth crack, the amplitude of periodical impulses increased as the crack depth increased, the rotate frequency and its harmonic frequencies are sensitive to the tooth crack.